Constant Ductility Site-Specific Yield Point Spectra for Seismic Design - Duofa Ji; Weiping Wen; Changhai Zhai (Advances in Civil Engineering)
Displacement-based seismic design (DBSD) is an iterative process because the strength and stiffness of a structure are needed to be adjusted in order to achieve a specific performance level, which is extremely inconvenient for designers in practice. Yield point spectra-based seismic design is treated as an alternative design method in which yield displacement as a basic parameter will not lead to an iterative process even though the lateral strength or stiffness of a structure changes during the whole design process. Along this line, this study focuses on investigating the yield point spectra (YPS) for structures located at different soil sites. YPS are computed for EPP systems under 601 earthquake ground motions. YPS for four soil sites are quantitatively analyzed by considering the influence of the vibration period, ductility factor, damping ratio, postyield stiffness ratio, and P-delta effect. The results indicate that compared with the effects of the damping ratio, the effects of the postyield stiffness ratio and P-delta effect on YPS are more profound. Finally, a prediction equation is proposed accounting for four soil sites and six ductility factors.